2022
DOI: 10.3389/fcimb.2022.719829
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Associated With Effectiveness And Responsiveness to Mindfulness-Based Cognitive Therapy in Improving Trait Anxiety

Abstract: ObjectiveMindfulness-based interventions have been widely demonstrated to be effective in reducing stress, alleviating mood disorders, and improving quality of life; however, the underlying mechanisms remained to be fully understood. Along with the advanced research in the microbiota-gut-brain axis, this study aimed to explore the impact of gut microbiota on the effectiveness and responsiveness to mindfulness-based cognitive therapy (MBCT) among high trait anxiety populations.DesignA standard MBCT was performe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
(53 reference statements)
3
21
0
2
Order By: Relevance
“…The abundances of all of these negatively correlated with 4-EPS. Significantly lower abundances of Blautia were found in the gut microbiota of people with high trait anxiety compared with healthy controls [ 10 ]. Because Blautia were significantly increased when dogs consumed the control/test foods in this study, they may shift the gut microbiome toward one associated with a less anxious state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundances of all of these negatively correlated with 4-EPS. Significantly lower abundances of Blautia were found in the gut microbiota of people with high trait anxiety compared with healthy controls [ 10 ]. Because Blautia were significantly increased when dogs consumed the control/test foods in this study, they may shift the gut microbiome toward one associated with a less anxious state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some dogs may exhibit behavioral phenotypes (canine dysfunctional behavior) similar to autism spectrum disorders (ASD) in human beings, including repetitive motions such as tail chasing as well as trance-like behavior [ 7 , 8 ]. Some work has been done to characterize the microbiome in people and dogs with anxiety or ASD [ 9 , 10 , 11 , 12 ]. Several studies have shown that transplantation of fecal microbiota from patients with a variety of psychiatric conditions into germ-free mice appears to result in the development of these conditions in the mice as measured by behavioral and physiological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…LEfSe analysis showed that Romboutsia in genus level was the characteristic bacteria after treatment with SJW. Significant overgrowth of Romboutsia has been found among high trait anxiety populations, as well as depression patients ( Zheng et al, 2021 ; Wang et al, 2022 ). Lactobacillus was observed as the species with significant differences in abundance after treatment with SG.…”
Section: Discussionmentioning
confidence: 99%
“…In full accordance with our results, DSS-induced colitis decreases the richness and diversity of the gut microbiota, both of which were reversed by the CW formula, highlighting its contribution to the remodeling of gut microbiota. An imbalanced gut commensal flora often begins with an increased prevalence of Proteobacteria and Bacteroides thetaiotaomicron, which have been considered potential diagnostic signatures of dysbiosis, depression, and colitis ( Shin et al, 2015 ; Wang et al, 2022 ), and the CW therapy considerably suppressed their colonization. Moreover, DSS treatment induced the colonization of the genera Escherichia and Shigella , which is involved in the development of UC into CAC ( Tang et al, 2020 ), which was also inhibited by CW treatment.…”
Section: Discussionmentioning
confidence: 99%